Tshokologo ka tirišo ya maina a baanegwa: Tebelelogare ya Mahlatse a Madimabe ka O.K. Matsepe - Seanego, James (Verbum et ecclesia, 2025)
Conversion through the use of character naming: An intertextual reading of O.K. Matsepe’s Mahlatse a Madimabe. The theme of conversion has received the desired attention by scholars in the field of theology. Other disciplines have done so little in examining this paramount subject within the society. This intertextual study seeks to investigate how conversion as a theological theme contributes towards the development of literary productions. By sampling O.K. Matsepe’s sunset narrative, Mahlatse a Madimabe , the article unravels how the theme of conversion is portrayed through the application of character names. Following qualitative methods of research, the article used intertextuality as its theoretical framework to thematically analyse the application of Matthew 3 verse 2 and Matthew 19 verse 14 as scriptures which Matsepe applied in naming his literary characters. The findings demonstrated the influence of Biblical verses in shaping themes found within literary works. Intradisciplinary and/or Interdisciplinary implications: In its nature, this study finds itself being located within the ambits of fields of literature and theology. It contributes to the limited body of research exploring the intersection of language and theology scholarship through an intertextual analysis of verses from Matthew scriptures.